Facile synthesis of a luminescent carbon material from yogurt for the efficient photocatalytic degradation of methylene blue. Issue 39 (7th September 2022) - Bhatti, Muhammad Ali; Tahira, Aneela; Shah, Aqeel Ahmed; Aftab, Umair; Vigolo, Brigitte; Khattab, Amira R.; Nafady, Ayman; Halepoto, Imran Ali; Tonezzer, Matteo; Ibupoto, Zafar Hussain
Abstract : Left hand side: structural and optical aspects of the as-prepared carbon material from yogurt. Right hand side: the absorbance spectra of methylene blue degradation using the as-prepared carbon material from yogurt. Abstract : The present study is focused on yogurt as a simple, inexpensive, abundant, and green source for the preparation of luminescent carbon material for enhancing the photodegradation of methylene blue (MB). It introduces an ecological and sustainable approach for the large-scale production of carbon material using the direct thermal annealing of yogurt in a muffle furnace. The size of the as-prepared carbon material is about 200–300 nm, with average particle size distribution of 355 nm. The material exhibits clear luminescence under illumination with ultraviolet light. The synthesized carbon material shows an outstanding degradation functionality of MB under the irradiation of ultraviolet (UV) light in aqueous media. Various dye degradation parameters such as initial dye concentration, catalyst dose, pH of dye solution, and scavenger effects have been investigated. The optimum MB concentration was found to be 2.3 × 10 −5 M with a degradation efficiency of 94.8%. The degradation was highly enhanced at pH 11 with a degradation efficiency of 98.11%. The degradation of MB under highly alkaline conditions was mainly governed by the high amount of hydroxyl radicals. Furthermore, the scavenger study confirmed that the hydroxyl radicals were mainly involved in the degradation process. The degradation kinetics of MB followed first order kinetics with large values of rate constant. The reusability was also studied to ensure the stability of the as-prepared carbon material during the degradation of MB. The preparation of carbon materials with efficient photosensitivity for the degradation of organic dyes from yogurt shows a green and innovative methodology. Therefore, it can be of great interest for future studies related to energy and environmental applications.